VD_FINDINFO AI 44/13 - 90/2015 vom 13. April 2015 - VD Tribunal cantonal (2015)
AIASSURANCE, RENTE D'INVALIDITÉ, TROUBLE SOMATOFORME DOULOUREUX, FORCE PROBANTE, RÉVISIONPRESTATION D'ASSURANCE | 16 LPGA, 17 LPGA, 6 LPGA, 7 LPGA, 8 LPGA